Hypoxia-inducible factor-2α is an essential catabolic regulator of inflammatory rheumatoid arthritis. - Je-Hwang Ryu; Chang-Suk Chae; Ji-Sun Kwak; Hwanhee Oh; Youngnim Shin; Yun Hyun Huh; Choong-Gu Lee; Yong-Wook Park; Churl-Hong Chun; Young-Myeong Kim; Sin-Hyeog Im; Jang-Soo Chun (PLoS Biology)
Rheumatoid arthritis (RA) is a systemic autoimmune disorder that manifests as chronic inflammation and joint tissue destruction. However, the etiology and pathogenesis of RA have not been fully elucidated. Here, we explored the role of the hypoxia-inducible factors (HIFs), HIF-1α (encoded by HIF1A) and HIF-2α (encoded by EPAS1). HIF-2α was markedly up-regulated in the intimal lining of RA synovium, whereas HIF-1α was detected in a few cells in the sublining and deep layer of RA synovium. Overexpression of HIF-2α in joint tissues caused an RA-like phenotype, whereas HIF-1α did not affect joint architecture. Moreover, a HIF-2α deficiency in mice blunted the development of experimental RA. HIF-2α was expressed mainly in fibroblast-like synoviocytes (FLS) of RA synovium and regulated their proliferation, expression of RANKL (receptor activator of nuclear factor-κB ligand) and various catabolic factors, and osteoclastogenic potential. Moreover, HIF-2α-dependent up-regulation of interleukin (IL)-6 in FLS stimulated differentiation of TH17 cells-crucial effectors of RA pathogenesis. Additionally, in the absence of IL-6 (Il6-/- mice), overexpression of HIF-2α in joint tissues did not cause an RA phenotype. Thus, our results collectively suggest that HIF-2α plays a pivotal role in the pathogenesis of RA by regulating FLS functions, independent of HIF-1α.